2020
DOI: 10.3390/su122410522
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Wastewater Treatment Plant Processes Efficiency Using Statistical Tools

Abstract: The paper presents modelling of wastewater treatment plant (WWTP) operation work efficiency using a two-stage method based on selected probability distributions and the Monte Carlo method. Calculations were carried out in terms of sewage susceptibility to biodegradability. Pollutant indicators in raw sewage and in sewage after mechanical treatment and biological treatment were analysed: BOD5, COD, total suspended solids (TSS), total nitrogen (TN) and total phosphorus (TP). The compatibility of theoretical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…It was only after more than one month of continuous operation that the reduction achieved a substantial, consistent level exceeding 90% (Figure 6). In the studies [27] conducted by other researchers, it was observed that the BOD 5 level in wastewater following a settling tank reached 774.7 mg O 2 /dm 3 . In contrast, our investigations indicated a BOD 5 level not exceeding 120 mg O 2 /dm 3 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It was only after more than one month of continuous operation that the reduction achieved a substantial, consistent level exceeding 90% (Figure 6). In the studies [27] conducted by other researchers, it was observed that the BOD 5 level in wastewater following a settling tank reached 774.7 mg O 2 /dm 3 . In contrast, our investigations indicated a BOD 5 level not exceeding 120 mg O 2 /dm 3 .…”
Section: Resultsmentioning
confidence: 92%
“…Throughout the four-month research period, the 60 cm foam filter consistently achieved substantial reductions of 60-80% in pollutants, including organic compounds and bacteria, demonstrating its superior performance. The evaluation of materials used in wastewater removal is crucial for addressing concerns related to process efficiency [27], environmental sustainability [32][33][34], and public health [35]. Preventing the formation of stagnant zones within the filtration bed is essential for effective wastewater management systems [36], especially in the context of a circular economy [36], particularly within urban wastewater management systems [37].…”
Section: Resultsmentioning
confidence: 99%
“…BOD 5 /TN is the main indicator for identifying the capability of biological nitrogen removal in WWTP [8]. Theoretically, BOD 5 /TN > 2.86 indicates that TN can be effectively removed in any type of wastewater treatment process due to the presence of DO competing with nitrate for an electron donor, and the corresponding BOD 5 /TN ratio must be higher than 5.0 to achieve efficient TN removal in the practical operation of WWTPs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the ef nia nitrogen was less than 3.0 mg/L with the increase in temperature. BOD5/TN is the main indicator for identifying the capability of biolog removal in WWTP [8]. Theoretically, BOD5/TN > 2.86 indicates that TN can removed in any type of wastewater treatment process due to the presence o ing with nitrate for an electron donor, and the corresponding BOD5/TN ater 2022, 14, x FOR PEER REVIEW higher than 5.0 to achieve efficient TN removal in the practical operation of ure 6 shows that the average value of BOD5/TN is approximately 3.0 and th of BOD5/TN > 5 is only 5%.…”
Section: Resultsmentioning
confidence: 99%
“…The inapplicability of this distribution is due to the homogeneous nature of this function. As Stain and Keblis [67], Pereira et al [68], and Mły ński et al [69] have stated in their studies, the Triangular distribution is described by the parameters of the upper and lower limits, i.e., the most probable maximum and minimum values, respectively. In the case of wastewater, the values of the individual quality parameters depend on many factors that vary over time.…”
Section: Fitting the Theoretical Distributionsmentioning
confidence: 91%